Two new species of Culicoides Latreille (Diptera: Ceratopogonidae) from the Gangetic Plains of West Bengal, India with a key to the Indian species. (3rd July 2021) - Chatterjee, Somnath; Brahma, Shubhranil; Hazra, Niladri
ABSTRACT: Two species, Culicoides obtusus sp. nov . of the subgenus Monoculicoides Khalaf and C. cornus sp. nov . of the Shermani group Wirth & Hubert are discovered from Kushmundi, Dakshin Dinajpur, Narayanpur, Birbhum, and Burdwan Town, Purba Bardhaman respectively of the Gangetic Plains of West Bengal, India with illustrations and microphotographs. The pupal stages of C. cornus sp. nov . were reared to adults of both sexes in the laboratory condition while members of both sexes of C. obtusus sp. nov . were collected using light trap as well as one pupa reared to get one adult female under the laboratory conditions. Identification of taxa is made following relevant literature and specimens are present housed in the Entomology Division, Department of Zoology, University of Burdwan. Information on the bionomics of the species, an inventory of Indian species of Culicoides and a key to the 73 Indian species of the genus are provided. urn:lsid:zoobank.org:pub:16BB3BAF-AA32-4316-AE79-8727BD4C33C5